Diagnosing syntax - Cheng, Lisa Lai Shen; Corver, Norbert, 1963- (Oxford studies in theoretical linguistics ;, 2013)
Drawing on the expertise of over 20 leading scholars and their empirically rich data, this book presents current thoughts on and practical answers to, the question: What are the diagnostic signs, techniques and procedures that can be used to analyse natural language syntax?